A novel robust active damping control strategy based on H∞ loop shaping for the grid-tied LCL inverter - Sang, Wenju; Guo, Wenyong; Xu, Gang; Wei, Tongzhen; Shi, Changli; Liu, Zongjie; Xue, Han; He, Zhenning; Li, Junzhi; Shen, Jiazhen; Min, Ruiqi; Song, Shaobo; et al. (Frontiers in Energy Research, 2024)
LCL-type grid-connected inverters have been widely used in renewable power generation due to their advantages such as small size and low cost. However ， the LCL filter has a problem of insufficient damping, which may lead to power system instability. Currently, two common methods are used to address this problem: passive damping (PD) and active damping (AD). PD methods suppress resonance by adding resistors to the LCL filter, but this approach increases system losses. AD methods enhance damping through control to suppress resonance. Nevertheless, existing AD methods are often significantly affected by grid-side inductance perturbation, resulting in insufficient robustness. To address this issue, this paper proposes a novel robust active damping (RAD) control strategy based on H∞ loop-shaping. Simulation analysis and experimental research show that the RAD control method exhibits superior robustness compared with the traditional capacitor current active damping control.